Perancangan Sistem Pengontrolan Dan Monitoring Pengaliran Nutrisi Pada Tanaman Hidroponik Berbasis Arduino Secara Otomatis - Shiddiq Thamrin; Oriza Candra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
Hydroponics is a method of cultivating agriculture without using soil as a medium, but instead using water as a growing medium. So that hydroponic cultivation can take advantage of narrow land. But this hydroponic cultivation also has its advantages and disadvantages. The advantages of cultivating with hydroponics are, it does not require soil, it can be done on narrow land, the quality of the plants is cleaner because it does not use soil, the plant growth is faster, the risk of plants being attacked by pests and diseases will be smaller. Meanwhile, the disadvantages of hydroponic cultivation are that it requires extra precision and monitoring. In farming with the hydroponic method, we must really pay attention to and control the nutrients given to plants, including the concentration of nutrients in plants. if not careful and monitor regularly, it will affect the growth of plants. This final project aims to control the concentration of nutrients and flow in hydroponic plants automatically. This tool consists of input received via the TDS sensor, RTC sensor and output in the form of a circulation pump, and nutrient pump A and nutrient B then Arduino as the data sender.